The word exchange a novel - Graedon, Alena (New York Anchor Books, 2015)
A fiendishly clever dystopian novel for the digital age, The Word Exchange is a fresh, stylized, and decidedly original debut about the dangers of technology and the power of the printed word
15
Keywords: Missing persons -- Fiction; Technology -- Fiction; Young women -- Fiction